Analisis Manajemen Risiko pada UMKM Apa Ya Food - Karimah, Nur Rafidah; Arrahman, Hajar Chair; Rahmawati, Siti (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Pempek, a traditional delicacy from Palembang, Indonesia, is made from finely ground fish mixed with tapioca flour and shaped into various forms such as pempek kapal selam and pempek lenjer. Its preparation involves mixing ingredients, shaping, and boiling, often served with cuko, a sweet, sour, and spicy sauce that enhances its flavor. Pempek is not only delicious but also nutritious, high in protein from fish. Dimsum, originating from China, has been adapted into diverse variations in Indonesia. Typically consisting of a dough filled with meat, vegetables, or other ingredients, dimsum is either steamed or fried. Known for its variety, it is often enjoyed as a snack or side dish during gatherings. Meanwhile, snacks in Indonesia encompass a wide range of small bites that can be enjoyed anytime, including chips, traditional snacks like risoles and pastel, and moist cakes. These snacks feature a variety of flavors, from sweet to savory, and frequently use local ingredients such as cassava, glutinous rice, and coconut. All three food categories pempek, dimsum, and snacks are not only popular among locals but are also gaining recognition internationally. Through innovations in recipes and presentation, they continue to evolve to suit modern consumer tastes.